A study of maternal near miss cases at tertiary medical college of Jharkhand, India - Kamal, Samarina; Roy, Priyankur; Singh, Shashibala; Minz, Jacinta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Maternal near miss is said to have occurred when women presented with life threatening complication during pregnancy, child birth and within 42 days after delivery, but survive by chance or good institutional care. For identifying near-miss cases five-factor scoring system was used. In 2009 WHO working group has standardized the criteria for selecting these cases. Methods: The study was conducted in the Department of Obstetrics and Gynecology at RIMS, Ranchi, Jharkhand, India, which is a tertiary care centre. For each case of near miss, data were collected on demographic characteristics including gestational age at the time of sustaining the near-miss morbidity, nature of obstetric complications, presence of organ-system dysfunction/failure, ICU admission and timing of near-miss event with respect to admission. Results: During the twenty-four months of the study period, 20000 deliveries at the institution and 480 women were identified as near-miss obstetrical cases by five factor scoring system. The prevalence of near-miss case in this study was 2.4%. Near-miss per 1000 delivery was 24%. Maternal death to near miss ratio was 1:7.2. The leading causes of maternal near miss were hemorrhage (42.5%) and hypertensive disorder of pregnancy (23.5%) The morbidity was high in unbooked cases. Conclusions: Maternal near miss is good alternative indicator of health care system.